Architectural patronage and the rise of the Ottomans - Yürekli, Z (Wiley, 2017)
This chapter takes a look at the role of other early Ottoman viziers in architectural practice is in order, before turning its attention to a multifunctional complex in Bursa, centered like its predecessors around a T-type hospice-mosque. Known as the Green Mosque, this building and its decoration, executed under the auspices of the vizier and architect Ivaz Pasha and the naqqash Ali b. Ilyas, has received great scholarly attention. The chapter demonstrates that the Green Mosque stands out as a particularly interesting case of a joint royal/vizierial undertaking. In a survey of Ottoman royal constructions, the decisive point of rupture with the local brick-and-stone construction techniques used in earlier Byzantine architecture would appear to be the early 1390s, when the T-type hospice-mosque complex and the Friday mosque of Bayezid I were constructed. The cases examined here confirm that the transfer of architectural and decorative knowledge between such distinct cultural and political centers was a reality.